ELECTRONIC PARLIAMENT: THE FUNCTIONS AND CREATION MECHANISMS - Константинівська, А. К. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Today, the issue of setting up an electronic parliament in Ukraine and its information and analytical support to ensure effective lawmaking activity is very relevant. In the western democratic world, parliaments widely use ICT (information and communication technologies) to optimize processes, increase accessibility, transparency, and enhanced reporting capabilities. Parliament is the main legislature institution, which demonstrates trends of new technologies, rapid exchange of information between divisions, the latest methods of processing and transmitting data in information systems. With the introduction of ICT in the parliament, key political values of the legislature should be strengthened, such as free access to information, openness, and transparency. E-democracy tools in the e-Parliament provide effective parliamentary functions, increase the quality of parliamentarism and the legislative process. New information systems make the legislature more efficient, and the tools of e-democracy and information and communication technologies enable citizens to be more involved in public affairs, through the possibility of indirect involvement in legislative initiatives. Adapting European experience can strengthen the institutional capacity of the Ukrainian parliament, deepen communication with civil society, introduce quality expert support and coordinate the adoption of new bills. This article examines the main functions of parliament with the use of ICT, tools of the electronic parliament and mechanisms for interaction with the external environment - media, experts and civil society. The main purpose of this study is to analyze world tendencies of the development e-Parliament and the possibility of introducing new electronic tools in the Verkhovna Rada of Ukraine.